2008
DOI: 10.4161/pri.2.2.7059
|View full text |Cite
|
Sign up to set email alerts
|

Left handed β helix models for mammalian prion fibrils

Abstract: We propose models for in vitro grown mammalian prion protein fibrils based upon left handed beta helices formed both from the N-terminal and C-terminal regions of the proteinase resistant infectious prion core. The C-terminal threading onto a b-helical structure is almost uniquely determined by fixing the cysteine disulfide bond on a helix corner. In comparison to known left handed helical peptides, the resulting model structures have similar stability attributes including relatively low root mean square devia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 67 publications
(74 reference statements)
1
24
0
Order By: Relevance
“…This location of b-strands is in agreement with that proposed for the b-sandwich model 6,15 but not with that suggested for the spiral model 60 or the published b-helix model. 11 An alternative b-helix model 61 comprising the C-terminal segment would be consistent with our solid-state NMR-data though.…”
Section: Discussionsupporting
confidence: 79%
“…This location of b-strands is in agreement with that proposed for the b-sandwich model 6,15 but not with that suggested for the spiral model 60 or the published b-helix model. 11 An alternative b-helix model 61 comprising the C-terminal segment would be consistent with our solid-state NMR-data though.…”
Section: Discussionsupporting
confidence: 79%
“…32,[41][42][43][44] The β helix 31,32 and the in-register models 44 have in common to propose the existence of a "prion domain" (as in yeast prions) 45 shorter than the whole PK-resistant segment, but they conflictingly locate it to efficient conversion as these amino acids were kept in our initial study, so as to minimize the eventual impacts on the formation of the last helix. Their removal from an otherwise well tolerated insert indeed impaired prion replication ( Table 1, compare lanes 1 and 8 or lanes 5 and 9).…”
Section: Insertions In the H2-h3 Domain And Structural Models Of Prp Scmentioning
confidence: 99%
“…In this respect some theoretical models such as formation of both an N and a C-terminal left hand β helix or domain swapping of the molecules, were also proposed. 41,43 Establishment of the 3D structure of PrP Sc arrangement as well as definition of the landscape of sequence elements critical for conversion and those susceptible to be modified remains a major challenge to at that place. However they do not exclude that the conversion process transform H3 and most of H2 into β strands.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Recent studies using molecular fitting or molecular dynamics have predicted the amyloidotic assembly of PrP Sc in trimeric, lefthanded parallel ␤-helical folds (15,43,45,49). The models predict that segment 100-KPSKP-104 of MoPrP forms an outward loop extending from the core ␤-helical architecture (15,26,49 (Fig. 3) and that the replacement of the MoPrP sequence 95 to 98 (HNQW) with the corresponding chicken sequence (YHNQ) did not affect conversion efficacy (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, an analysis by infrared spectroscopy indicated that PrP Sc was abundant in ␤-sheets (4), and a recent molecular-fitting approach using electron crystallographic density maps suggested an amyloidotic assembly in a trimeric, left-handed parallel, ␤-helical fold (15,52). Later, this model was further modified to include two ␤-helical turns per PrP Sc molecule, based on molecular dynamics (26). Alternatively, molecular dynamics followed by an experimental assessment indicated a spiral model (9,10).…”
mentioning
confidence: 99%